Leptin expression affects metabolic rate in zebrafish embryos (D. rerio) - Dalman, Mark R.; Liu, Qin; King, Mason D.; Bagatto, Brian; Londraville, Richard L. (Frontiers in Physiology, 2013)
We used antisense morpholino oligonucleotide technology to knockdown leptin-(A) gene expression in developing zebrafish embryos and measured its effects on metabolic rate and cardiovascular function. Using two indicators of metabolic rate, oxygen consumption was significantly lower in leptin morphants early in development (<48 hpf), while acid production was significantly lower in morphants later in development (>48 hpf). Oxygen utilization rates in <48 hpf embryos and acid production in 72 hpf embryos could be rescued to that of wildtype embryos by recombinant leptin coinjected with antisense morpholino. Leptin is established to influence metabolic rate in mammals, and these data suggest leptin signaling also influences metabolic rate in fishes.